A value-based design approach for base-isolated structural systems. Issue 1 (2nd January 2017) - Ramezani, Soheil; Ziyaeifar, Mansour
ABSTRACT: The main assumption in seismic design procedures for structural systems is to provide the building with a high level of structural performance, subjected to earthquake loads. Such demand for higher performance needs additional investment on the project. In this work by taking into account the socio-economical aspects of the project, a value-based design approach is used to rationalise the structural design procedure in terms of initial investment. Determination of value design point in this approach is based on providing the optimality criterion from a global perspective. According to the results of this study, while for hospitals located in small cities with no substitute functionality in case of earthquake incident using base isolation for the structural system is quite necessary, for large cities, construction of fixed-base hospitals can still be permitted. The study also shows that, in the countries with higher growth rate, the required structural capacity to deal with earthquake demands in value-based design approach is lower than that required for low growth rate regions.